2007
DOI: 10.1261/rna.574407
|View full text |Cite
|
Sign up to set email alerts
|

Mg2+ binding and archaeosine modification stabilize the G15–C48 Levitt base pair in tRNAs

Abstract: The G15-C48 Levitt base pair, located at a crucial position in the core of canonical tRNAs, assumes a reverse Watson-Crick (RWC) geometry. By means of bioinformatics analysis and quantum mechanics calculations we show here that such a geometry is moderately more stable than an alternative bifurcated trans geometry, involving the guanine Watson-Crick face and the cytosine keto group, which we have also found in known RNA structures. However we also demonstrate that the RWC geometry can take advantage of additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
101
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(112 citation statements)
references
References 80 publications
11
101
0
Order By: Relevance
“…The A-G base pair increases the C1′-C1′ distance by ∼1.5 Å, from 11.2 Å to 12.7 Å, and will have different stacking interactions (62), which may account for the differences in the C8-preQ 1 hydrogen bonds for the two riboswitches.…”
Section: Resultsmentioning
confidence: 99%
“…The A-G base pair increases the C1′-C1′ distance by ∼1.5 Å, from 11.2 Å to 12.7 Å, and will have different stacking interactions (62), which may account for the differences in the C8-preQ 1 hydrogen bonds for the two riboswitches.…”
Section: Resultsmentioning
confidence: 99%
“…This modification is found at position 34 in five H. volcanii tRNAs (Gupta 1984, Gupta 1986), but its function is unknown. It has been postulated that the conformational rigidity of this nucleoside could stabilize RNA molecules of thermophilic archaea (Kawai et al 1992, Bruenger et al 1993, Oliva et al 2007). Our data indicate that an H. volcanii strain with tRNA lacking ac 4 C remains viable.…”
Section: Discussionmentioning
confidence: 99%
“…The function of archaeosine in vivo has yet to be investigated but its location has led to the hypothesis that it may function in stabilizing the tertiary structure of the tRNA through global interactions between the D-loop and the T-stem and loop (Gregson et al 1993). The archaeosine biosynthetic pathway is complex and poorly characterized (Oliva et al 2007). It has been shown that 7-cyano-7-deazaguanine (preQ 0 ) is an intermediate in the pathway and is inserted into tRNA by a tRNA-guanine transglycosylase (TGT, EC 2.4.2.29) encoded by the tgtA gene (Bai et al 2000, Watanabe et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…This observation, along with the fact that fluorescence experiments (Rieder et al 2007 (Ottink et al 2007) on the guanine-free G-riboswitch also indicate the importance of Mg 2+ ions in proper folding of the aptamer domain even in the absence of a ligand. It may be mentioned here, that Mg 2+ ions are known to stabilize even intrinsically unstable base-pairing geometries, as in the case of the Levitt base pair in tRNA (Oliva et al 2007).…”
Section: The Role Of Magnesium Ionsmentioning
confidence: 98%